A multi-energy level agnostic simulation approach to defect generation. (October 2021) - Vici, Andrea; Degraeve, Robin; Kaczer, Ben; Franco, Jacopo; Van Beek, Simon; De Wolf, Ingrid
Highlights: Multi-energy level agnostic approach describes defects generation during time-dependent dielectric breakdown. Defect generation is both fluence and energy-carrier-driven. Considering the bond strength distribution, the accepted power-law trend for defect generation is naturally obtained by Monte Carlo simulations. Low-frequency AC time to-breakdown increased compared to DC. Abstract: Defect generation during time-dependent dielectric breakdown stress is investigated by a multi-energy level agnostic model. Monte Carlo simulations show that the characteristic power-law increase of the generated defects with stress time is readily obtained when considering distributed bond strengths. DC and AC unipolar simulations show the proportionality between the time-to-breakdown and the fluence and energy of the injected carriers. These results are consistent with the experimental observations of a fluence and energy-driven process in thin oxides.